The Rpv3-3 Haplotype and Stilbenoid Induction Mediate Downy Mildew Resistance in a Grapevine Interspecific Population - Vezzulli, Silvia; Malacarne, Giulia; Masuero, Domenico; Vecchione, Antonella; Dolzani, Chiara; Goremykin, Vadim; Mehari, Zeraye Haile; Banchi, Elisa; Velasco, Riccardo; Stefanini, Marco; Vrhovsek, Urska; Zulini, Luca; et al. (Frontiers in Plant Science, 2019)
The development of new resistant varieties to the oomycete Plasmopara viticola (Berk. & Curt) is a promising way to combat downy mildew (DM), one of the major disease threatening the cultivated grapevine (Vitis vinifera L.). Taking advantage of a segregating population derived from Merzling (a mid-resistant hybrid) and Teroldego (a susceptible landrace), 136 F1 individuals were characterized by combining genetic, phenotypic and gene expression data to elucidate the genetic bases of DM resistance and polyphenol biosynthesis upon P. viticola infection. An improved consensus linkage map was obtained by scoring 192 microsatellite markers. The progeny was screened for DM resistance and production of 42 polyphenols. QTL mapping showed that DM resistance is associated with the herein named Rpv3-3 specific haplotype and it identified 46 novel metabolic QTLs linked to 30 phenolics-related parameters. A list of the 95 most relevant candidate genes was generated by specifically exploring the stilbenoid-associated QTLs. Expression analysis of 11 genes in Rpv3-3+/- genotypes displaying disparity in DM resistance level and stilbenoid accumulation revealed significant new candidates for the genetic control of stilbenoid biosynthesis and oligomerization. These overall findings emphasized that DM resistance is likely mediated by the major Rpv3-3 haplotype and stilbenoid induction.